Virulence Factors and Phylogenetic Characteristics of Uropathogenic Eschericihia coli Strains Isolated in Saratov - A. V. Kazantsev; N. A. Osina; T. O. Glinskaya; O. N. Kosheleva; Yu. V. Maksimov; Z. L. Devdariani; A. N. Mikerov (Проблемы особо опасных инфекций, 2020)
Objective of this study was the molecular genetic characteristics of uropathogenic strains of Escherichia coli, isolated from urine of patients with urinary tract infections in Saratov City, in order to determine the phylogenetic groups and subgroups to which the strains belong, and to identify the genetic markers associated with virulence. Materials and methods. Molecular genetic characteristics of 102 strains of uropathogenic E. coli which were isolated from urine of patients with urinary tract infections, was performed. PCR was used to determine the frequency of oc-currence of genes (fimH, pap, sfa, afa, iha, irp2, iuc, iroN, hlyA, vat, usp, set-1, kpsMT, iss, cva, ompT) associated with factors of adhesion, iron intake, toxigenicity, resistance to action of serum (complement) and persistence, as well as belonging of studied strains to the specific phylogenetic groups and subgroups (by amplification of genes chuA,yjaA and TspE4.C2). Results and discussion. It was revealed that E. coli strains isolated from patients with urinary tract infections in Saratov city belonged to different phylogenetic groups and subgroups (A1, B1, B23, D3 и D2) and differed in their set of genes, which encode the basic virulence factors. At the same time, detection of uropathogenic E. coli which belong to the B23 subgroup was the most frequent. Moreover, the strains of this phylogenetic subgroup differed from others in the largest set of genes which encode virulence factors of the etiological agent. In all studied strains of uropathogenic E. coli which belong to different phylogenetic groups and subgroups the presence of genes responsible for the synthesis of siderophores (irp2, iuc, iroN), resistance and persistency (ompT) and adhesion factors (fimH, iha) was revealed. Therefore, strains of uropathogenic E. coli isolated from patients with urinary tract infections in Saratov city belong to different phylogenetic groups and subgroups and have a different set of genetic markers of virulence that can affect the degree of pathogenicity of the etiological agent, and the course of the disease.